Friction and wear performance of HFCVD nanocrystalline diamond coated silicon nitride ceramics - Abreu, C. S. (2006)
Silicon nitride (Si3N4) ceramics were selected as substrates due to their thermal and chemical compatibility to diamond that ensure the adequate NCD adhesion for mechanical purposes. NCD deposition was performed by hot-filament chemical vapour method (HFCVD) using Ar/H2/CH4 gas mixtures. The tribological assessment of homologous pairs of NCD films was accomplished using reciprocating ball-on-flat tests using NCD coated Si3N4 plates and balls. The friction evolution is characterized by an initial running-in regime with a sharp peak up to 0.70, shortly followed by a steady-state regime identified by very low friction coefficients values (0.02–0.03). The threshold load prior to delamination depends on the starting surface roughness of the substrates and attains a value of ¨40 N. In terms of wear performance, the NCD films reveal a mild wear regime (K~10-7 mm3 N-1 m-1) for self-mated dry sliding conditions.